2014
DOI: 10.18052/www.scipress.com/ilns.8.7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fiber Length on Tensile Properties of Polyester Resin Composites Reinforced by the Fibers of <i>Sansevieria trifasciata</i>

Abstract: This paper presents the study of the tensile properties of Sansevieria trifasciata -fiber (here after called STF) reinforced polyester composites. The composite sample was fabricated with five different fiber lengths of STF (2, 4, 6, 8 and 10 mm). The fabrication was made by hand lay-up technique. Mechanical properties were determined using tensile testing. An interact between fiber and matrix was observed from the SEM (scanning electron microscope) micrographs. The study reveals that the tensile strength incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The laboratory test results of the study were similar to the reports of Yang and Reddy [4], Ververis et al [5], Fagbemigun et al [6], Sankar et al [7], and Kanimozhi [8].…”
Section: Resultssupporting
confidence: 87%
“…The laboratory test results of the study were similar to the reports of Yang and Reddy [4], Ververis et al [5], Fagbemigun et al [6], Sankar et al [7], and Kanimozhi [8].…”
Section: Resultssupporting
confidence: 87%
“…More specifically, some studies have shown that the mechanical properties of flax, hemp, jute, and sisal fibers can compete with those of glass fibers (Gurunathan et al, 2015). Other research has shown that tensile and modulus properties tend to increase with increasing fiber volume fractions (Sankar et al, 2014). Although glass fiber is the primary reinforcement material used in composites for automotive applications, biocomposites have shown good potential for future development.…”
Section: Introductionmentioning
confidence: 99%
“…The density, maximum peak temperature and tensile strength, young’s modulus and elongation were calculated and compared with other natural fibers. Fiber length was a major factor to decide the tensile properties of Sanevieria trifasciata fiber composites which was studied and reported in Sankar et al (2014). In this study, 10 mm length of fiber gave high tensile strength but it was reversed in the case of elongation at break.…”
Section: Introductionmentioning
confidence: 70%